Genre preferences in Reading Comprehension materials in first level English book of Senior High School - Panjaitan, Heldina Irawati; Togatorop, Nofita Romianna; Saragih, Erikson (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2019)
This study aimed to know genre preferences in the reading comprehension material in first level English book of senior high school. This study, which is employed a qualitative-narrative technique with no statistical analysis, described some material for reading comprehension material, such as descriptive text, narrative text, and recount text. This study revealed that the reading comprehension materials in first level English book of senior high school was presented into ten reading comprehension materials. Such as: self-introduction, expression of compliment, plans and intention, descriptive text I and II, announcement, past and present prefect tense, recount text, narrative text, and song. It also revealed that genre preferences in the reading comprehension materials in first level English book senior high school was presented into three genre preferences: descriptive text, recount text, and narrative text.Â DOI:10.26905/enjourme.v4i2.3708